Identity and crypto-racism: Len Bloom takes issue with Kevin Durrheim’s review of his book (PINS 27, 2001) - Bloom, Len (PINS-Psychology in Society, 2026)
I wonder if I’m the best person to comment on Kevin Durrheim’s (2001) mostly friendly and favourable review of my book Identity and ethnic relations in Africa (PINS, 27, 123-125)? I disagree that universalism and humanism are "of a previous age", and I resent his claim to have found "traces of crypto-racism".